Complying with Unwelcome Rules? Developing Countries and the TRIPs Agreement - S. Winanty, Poppy (Affiliated to Student Bar Association, National Law School of India Unuversity, 2009)
The Trade Related Intellectual Property Rights (TRIPs) Agreement, concluded as part of the Uruguay Round of multilateral trade negotiations, is a particularly ambitious international agreement in that aims to seta common floor for intellectual property protection in all World Trade Organization (WTO) members. Leading developing countrygovernments vigorously resisted the conclusion ofthe agreement for philosophical and economic reasons, but under heavy pressure from developed countrygovernments eventually accepted it. Despite their objections, almost all developing countrygovernments have taken steps to comply with the TRIPS Agreement, many have done so before they were required to and many adopted more rigorous IPR rules than strictly required by TRIPs. This article seeks to explain this puzzle by testing explanations compliance derived from realism, which emphasizes the importance ofgreat power coercion; neo-liberalism, which stresses coercion, but also the costs associated with reciprocal withdrawal of benefits and a loss ofreputation as a reliable partner; and constructivism, which tends tofocus on the legitimacyofthe international rule. It finds that none of these explanations accounts for the observed variance and argues for closer anal ysis of the domestic politics ofdeveloping countries' compliance.